2015
DOI: 10.1111/jace.13751
|View full text |Cite
|
Sign up to set email alerts
|

Development and Durability Testing of a Low‐Temperature Sintering Bi–Si–Zn Oxide Glass Composite Material (GCM) 129I Waste Form

Abstract: The capture and safe storage of radiological iodine ( 129 I) from nuclear fuel reprocessing is of concern due to its long half-life and potential mobility in the environment. The development of durable waste forms in which to store captured iodine requires materials that are both compatible with the iodine capture phases and durable to repository environments. To that end, Sandia is developing a low-temperature sintering Bi-Si-Zn oxide glass composite material (GCM) waste form and herein presents results of du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We believe that incorporation of the ORNL AgI-MOR in the GCM, with silver flake added to capture volatilized iodine to form AgI, will result in a durable waste form on par with that recorded with AgI-MOR incorporation into the GCMs. 8 Furthermore, past studies of ours shown that the iodine is better entrapped in the Ag-MOR when a number of other variables are introduced to the zeolite Mordentie for iodine capture. These include: (1) use of a nonnatural/geologic MOR (which is much more highly crystalline and does not contain many…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We believe that incorporation of the ORNL AgI-MOR in the GCM, with silver flake added to capture volatilized iodine to form AgI, will result in a durable waste form on par with that recorded with AgI-MOR incorporation into the GCMs. 8 Furthermore, past studies of ours shown that the iodine is better entrapped in the Ag-MOR when a number of other variables are introduced to the zeolite Mordentie for iodine capture. These include: (1) use of a nonnatural/geologic MOR (which is much more highly crystalline and does not contain many…”
Section: Discussionmentioning
confidence: 91%
“…and density = 5.675 g/cm 3 ) 3 has a low solubility in water, 3 x 10 -6 g/L at 20°C 3 [4][5][6][7] They are easier and less expensive to prepare than conventional ceramics but also offer high durability, as shown in our recent work. 8 In our previous reports 5-8 on I 2 -loaded Ag-MOR, we identified a commercially available low-temperature sintering glass powder based on silicon and bismuth oxides that sinters to full density at 550C and has excellent durability. To prevent surface/bulk chemisorbed I 2 vapor from escaping from the zeolite during GCM sintering, additional Ag flake was added to the GCM mixture to capture the desorbing I 2 vapor.…”
Section: Introductionmentioning
confidence: 99%
“…This feature is especially useful for addressing the low-temperature processing objective for a technetium secondary waste stream. Waste loadings of 20-25% are typical in research publications on iodide encapsulation, which are described below [Mowry 2015, Garino 2011]. There are a large number of glasses in Appendix B with reported sintering temperatures below 700 °C, and an even greater number that have softening points in the 400-500 °C range, a good indicator of their potential to be used in GCMs for technetium.…”
Section: Low Temperature Glass-ceramic Materials Preliminary Process mentioning
confidence: 99%
“…Specifically, for an AgI-mordenite monolith containing 5 wt% iodide exposed to near-neutral water, the authors reported an average of 19.5 ppm of silicon in the effluent in the MCC-1 test (pH 8.2-8.3) and 53.1 ppm in the PCT-B test (pH 7.5-7.6). Using the density and surface area estimates provided in the Experimental section of the paper, the average leach rates for silicon were 0.24 g Si/m 2 /day (MCC-1) and 0.081 g Si/m 2 /day (PCT-B) [Mowry 2015].…”
Section: Low Temperature Glass-ceramic Materials Preliminary Process mentioning
confidence: 99%
See 1 more Smart Citation